Mediator Liability 23 Years Later: The “Three C’s” of Case Law, Codes, & Custom - Schulz, Jennifer (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2023)
In 2001, the Ottawa Law Review published my review of Canadian and American cases that considered and rejected negligence liability for mediator malpractice. Now, 23 years later, I have reviewed the case law from Canada, the United States, England, Australia, New Zealand, and South Africa and found that courts are still not holding mediators liable, even where their conduct is negligent. The case law states that mediators have a duty to act impartially, without conflicts of interest, without bias, and in a manner that allows parties’ rights to self-determination. However, there are no decisions that definitively outline a duty of care for mediators. Instead, courts occasionally revoke agreements reached in mediations where the mediator behaved poorly. I advocate for standards of care to be created so that in the future, mediators whose practice is substandard can be found negligent. My argument is that by combining the “three C’s,” case law (case law), mediator codes of conduct (codes), and the tort law principle of custom (custom), a future common law court will be able to articulate legal standards of care for mediators.